The largest bright ULX population in a galaxy: X-ray variability and luminosity function in the Cartwheel ring galaxy. Issue 1 (29th March 2023) - Salvaggio, Chiara; Wolter, A; Belfiore, A; Colpi, M
ABSTRACT: We analyse all the available Chandra observations of the Cartwheel galaxy and its compact group, taken between 2001 and 2008, with the main aim of addressing the variability in the X-ray band for this spectacular collisional ring galaxy. We focus on the study of point-like sources, in particular we are interested in ultraluminous X-ray sources (ULXs; L X ≥ 10 39 erg s −1 ), that we treat as a class. We exploit archival XMM–Newton data to enrich the study of the long-term variability, on time-scales of months to years. We find a total of 44 sources in the group area, of which 37 in total are ULXs positionally linked with the galaxies and of which we can study variability. They are 29 in the Cartwheel itself, seven in G1, and one in G3. About one-third of these 37 sources show long-term variability, while no variability is detected within the single observations. Of those, five ULXs have a transient behaviour with a maximum range of variability ( L max / L min ) of about one order of magnitude and are the best candidate neutron stars. The X-ray luminosity function (XLF) of the point-like sources remains consistent in shape between the Chandra observations both for the Cartwheel galaxy itself and for G1, suggesting that flux variability does not strongly influence the average properties of the population on the observation time-scales.